ANALISIS PERMINTAAN IKAN LELE (Clarias sp) OLEH PEDAGANG PECEL LELE DI KOTA BANDAR LAMPUNG - Mukti Arta Sari; Ktut Murniati; Wuryaningsih Dwi Sayekti (Lampung University, 2017)
The objectives of this research were to know demand pattern of catfish (Clarias sp) and the factors that affected the demand of catfish (Clarias sp) by pecel lele vendors in the city of Bandar Lampung. This research was conducted in Bandar Lampung city by survey method. Data collection was carried out in November 2015 through to May 2016. The location was chosen purposively. There were 51 respondents of pecel lele vendors chosen by simple random sampling. The research data was analyzed by descriptive statistisc analysis and regression analysis. The results obtained from this study was the catfish demand by pecel lele vendors at Bandar Lampung had buying frequency atseven times a week with the purchase amount of catfish as much as 13-35 kilograms per week. Type of catfish that was widely purchased by pecel lele vendors was sangkuriang, and the sellers usually buy catfish at the suppliers who delivered catfish to the merchant. Factors that affected the catfish demand by pecel lele vendors at Bandar Lampung was catfish price, the portion of pecel lele, variety numbers of sold food, output prices (pecel lele), business income and business scale dummy. Key words: catfish, demand pattern, pecel lele vendors